Decreased Choroidal Vascular Index in Idiopathic Intracranial Hypertension - Hang Wang; Rui Wang; Le Cao; William Robert Kwapong; Ruishan Liu; Fayun Hu; Bo Wu (Brain and Behavior)
ABSTRACT Introduction We aimed to explore the difference in choroidal vascular parameters using swept‐source optical coherence tomography (SS‐OCT) in patients with idiopathic intracranial hypertension (IIH) compared to controls. We also explored the ability of the choroidal parameters to reflect elevated intracranial pressure (ICP) in patients with IIH. Methods This observational study recruited patients diagnosed with IIH and healthy controls. A lumbar puncture was performed for ICP measurement. All the participants underwent OCT examinations. The choroid was automatically segmented and imaged by the OCT tool. The parafoveal choroidal vascular volume (CVV) and choroidal vascular index (CVI) were calculated in 3 mm annulus and 6 mm annulus. Results A total of 80 patients with IIH (34.67 ± 11.00 years; 37.50% males) and 92 controls (34.50 ± 12.08 years; 36.96% males) were included in the final analysis. Patients with IIH had higher BMI (< 0.001) and poor visual acuity (< 0.001) compared with controls. Patients with IIH demonstrated significantly lower parafovea CVI in both annuluses (p = 0.003 for 3 mm annulus, p = 0.001 for 6 mm annulus) compared to controls. Mean parafovea CVI in both annuluses was significantly correlated with ICP level (p = 0.014 for 3 mm annulus, p = 0.015 for 6 mm annulus). The combination of CVV and CVI in a 6 mm annulus demonstrated the highest diagnostic value with a mean AUC of 0.818. Conclusion CVI may serve as a potential marker for identifying IIH and reflecting ICP changes.